Severe meningo-/encephalitis after daclizumab therapy for multiple sclerosis. (October 2019) - Stork, Lidia; Brück, Wolfgang; von Gottberg, Phillip; Pulkowski, Ulrich; Kirsten, Florian; Glatzel, Markus; Rauer, Sebastian; Scheibe, Franziska; Radbruch, Helena; Hammer, Eckhard; Stürner, Klarissa H; Kaulen, Barbara; et al.
Background: Daclizumab is a monoclonal antibody that binds the high-affinity interleukin-2 receptor and was approved for the treatment of relapsing multiple sclerosis. Due to severe inflammatory brain disorders, the approval was suspended in March 2018. Objective and Methods: This retrospective cohort study summarizes clinical, laboratory, radiological, and histological findings of seven patients who developed meningo-/encephalitis after daclizumab therapy. Results: Patients presented with encephalitis and/or meningitis and suffered from systemic symptoms such as fever (5/7), exanthema (5/7), or gastrointestinal symptoms (4/7). Secondary autoimmune diseases developed. Blood analysis revealed an increase in eosinophils (5/7). Six patients fulfilled the diagnostic criteria for a drug reaction with eosinophilia and systemic symptoms (DRESS). Magnetic resonance imaging (MRI) showed multiple contrast-enhancing lesions, and enhancement of the ependyma (6/7), meninges (5/7), cranial or spinal nerves (2/7), and a vasculitic pattern (3/7). Histology revealed a pronounced inflammatory infiltrate consisting of lymphocytes, plasma cells and eosinophils, and densely infiltrated vessels. Most patients showed an insufficient therapeutic response and a high disability at last follow-up (median Expanded Disability Status Scale (EDSS) 8). Two patients died. Conclusion: Meningoencephalitis and DRESS may occur with daclizumab therapy. This potential lethal side effect is characterized by a dysregulated immune response. Our findings underline the importance of postmarketing drug surveillance.